Multiple MYB Activators and Repressors Collaboratively Regulate the Juvenile Red Fading in Leaves of Sweetpotato - Deng, Jiliang; Wu, Danning; Shi, Jie; Balfour, Kelly; Wang, Huafeng; Zhu, Guopeng; Liu, Yonghua; Wang, Jian; Zhu, Zhixin (Frontiers in Plant Science, 2020)
Juvenile red fading describes the phenomenon in plants whereby red young leaves gradually turn green as they mature. While this phenomenon is commonly observed, the underlying molecular mechanism is still obscure as the classic model plants do not exhibit this process. Here, the molecular mechanism for the loss of anthocyanins during juvenile red fading were explored in the sweetpotato (Ipomoea batatas L.) cultivar ‘Chuanshan Zi’. The MYB-bHLH-WDR (MBW) regulatory complexes for anthocyanins were examined with five stages of leaf development from C1 to C5. Alternating accumulation of anthocyanins and chlorophylls caused the leaf color change. Five anthocyanin components were identified by UPLC-MS/MS, and their contents were highest at stage C2. Transcriptomic analysis showed massive gene expression alteration during leaf development. The anthocyanin structural genes expressed in sweetpotato leaves were screened and found to be highly comparable with those identified in morning glories. The screened anthocyanin regulatory genes included one bHLH (IbbHLH2), one WDR (IbWDR1), three MYB activators (IbMYB1, IbMYB2, and IbMYB3), and five MYB repressors (IbMYB27, IbMYBx, IbMYB4a, IbMYB4b, and IbMYB4c). The expression trends of MYBs were key to the red fading process: the activators were highly expressed in early red leaves and were all accompanied by simultaneously expressed MYB repressors, which may act to prevent excessive accumulation of anthocyanins. The only antagonistic repressor, IbMYB4b, was highly expressed in green leaves, and may be critical for declined anthocyanin content at later stages. Further functional verification of the above transcription factors were conducted by promoter activation tests. These tests showed that the MBW complexes of IbMYB1/IbMYB2/IbMYB3-IbbHLH2-IbWDR1 not only activated promoters of anthocyanin structural genes IbCHS-D and IbDFR-B, but also promoters for IbbHLH2 and IbMYB27, indicating both hierarchical and feedback regulations. This study outlines the elaborate regulatory network of MBW complexes involving multiple MYBs which allow for the timely accumulation of anthocyanins in sweetpotato leaves. These results may also provide clues for similar studies of juvenile red fading in other plant species.